Harga Menjadi Murid Kristus: Eksposisi Historis-Kontekstual Berdasarkan Lukas 14:25-27 - Frans Aliadi (Jurnal Ilmiah Tafsir Alkitab, 2025)
This article discusses the demands of Jesus in Luke 14:25-27 regarding the cost of discipleship, which is often misinterpreted. Using an exegesis approach and Greek language analysis, this study explores the meanings of key terms such as misei (to hate) and pherei ton stauron (to carry the cross), as well as their theological implications. The study also compares various interpretive approaches, revealing that true discipleship is not just about faith acknowledgment, but also about sacrifice and total loyalty, involving a profound life commitment. By exploring linguistic, historical, and theological aspects, this article provides new insights into understanding this text. The research not only enriches the understanding of discipleship in biblical context but also its relevance to the lives of contemporary believers, emphasizing the importance of sacrifice and full commitment to Christ's calling in daily life for the sake of God's Kingdom.